The ratio of metabolically active versus total Mycolata populations triggers foaming in a membrane bioreactor. (1st April 2016) - Maza-Márquez, P.; Vílchez-Vargas, R.; Boon, N.; González-López, J.; Martínez-Toledo, M.V.; Rodelas, B.
Abstract: The abundance of total and metabolically active populations of Mycolata was evaluated in a full-scale membrane bioreactor (MBR) experiencing seasonal foaming, using quantitative PCR (qPCR) and retrotranscribed qPCR (RT-qPCR) targeting the 16S rRNA gene sequence. While the abundance of total Mycolata remained stable (10 10 copies of 16S rRNA genes/L activated sludge) throughout four different experimental phases, significant variations (up to one order of magnitude) were observed when the 16S rRNA was targeted. The highest ratios of metabolically active versus total Mycolata populations were observed in samples of two experimental phases when foaming was experienced in the MBR. Non-metric multidimensional scaling and BIO-ENV analyses demonstrated that this ratio was positively correlated to the concentrations of substrates in the influent water, F/M ratio, and pH, and negatively correlated to temperature and solids retention time. It the first time that the ratio of metabolically active versus total Mycolata is found to be a key parameter triggering foaming in the MBR; thus, we propose it as a candidate predictive tool. Graphical abstract: Highlights: Abundance of total and metabolically active Mycolata was evaluated in a MBR (qPCR). Mycolata abundances were linked to changes in variables influencing the MBR. The increase of the ratio of active versus total Mycolata was related to foaming.